HUBUNGAN STRES DENGAN KEJADIAN GOUT ARTHRITIS PADA LANSIA DI WILAYAH KERJA PUSKESMAS BOTANIA KOTA BATAM - Alba, Afif D; Fatrida, Dedi; Badar, Mawardi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
As a person ages, there is a tendency to decrease various functional capacities both at the cellular level and at the organ level which can lead to degeneration in line with the three aging processes. One of the degenerative diseases that are often suffered by the elderly is gout arthritis, which is an inflammatory joint disease, a factor that causes gout arthritis attacks, one of which is stress, stress is not only a stimulus or reaction but also an active factor that can affect stressors. This study aims to see the relationship between stress and the incidence of gout arthritis in the Botania Health Center Work Area, Batam City 2022. Method of this research is an analytical observational study with a case control design involving 60 respondents, with an elderly population at the Botania Health Center in 2022. Sampling using purposive sampling technique . The measuring instrument in this study was the Depression Anxiety Stress Scale (DASS 21) questionnaire and the “Medical Record” retrospective method. The results of study, most of the elderly who experience stress have a risk of developing gout. The results of the Chi-Square statistical test obtained a value (p value = 0.001 < 0.05), indicating that H0 was rejected and Ha was accepted with an Odds Ratio of 6.417. The conclusion is that there is a significant relationship between stress and the incidence of gout arthritis. So implementing a healthy lifestyle with stress control can be a preventive measure against various diseases that can attack the elderly.Keywords: Degenerative diseases, Stress, Gout Arthritis, Elderly, analytical observational